Jacob wants to make a graph to show the relationship between temperatures in Fahrenheit and degrees Celsius. He plots the following points:(11, −11.7), (15, −9.4), (25, −3.9), (35, 1.7), (45, 7.2)

He uses the following steps to plot the graph:


1.Label origin as (0, 0).
2.On x-axis, label Temperature in Fahrenheit.
3. On y-axis, label Temperature in degrees Celsius.
4.The scale on x-axis starts from 0 and goes up to 700 at intervals of 20.
5.The scale on the y-axis starts from −12 and goes up to 12 at intervals of 2.

Which of the following best describes the graph?

It will not be spread out horizontally across the entire coordinate plane because in Step 4, Jacob selected an incorrect scale on the x-axis.

It will not be spread out vertically across the entire coordinate plane because in Step 5, Jacob selected an incorrect scale on the y-axis.

It will not be spread out horizontally across the entire coordinate plane because in Step 2, Jacob plotted Fahrenheit instead of Celsius on the x-axis.

It will not be spread out vertically across the entire coordinate plane because in Step 3, Jacob plotted Celsius instead of Fahrenheit on the y-axis.

Answers

Answer 1
Answer: Answer: It will not be spread out horizontally across the entire coordinate plane because in Step 2, Jacob plotted Fahrenheit instead of Celsius on the x-axis.

Jacob confused the values, the first coordinate of the ordered pairs (which corresponds to the x-axis) is in Celsius and he used it as Farenheit.


Related Questions

16a +72 what is the answer
What is the end behavior of the polynomial function?
a certain hose delivers 5 gallons of water in 24 seconds, how much water will the hose deliver in 10 minutes
1/3*h(-8) h(x)= x^2 - 5x +7
Solve the equation 7-y-y=-1

CAN SOMEONE HELP PLEASE! A circle has center O(−2, −4) and radius 10. Which of the following points is on the circle?

Hint: d equals square root of left parenthesis x sub one minus x sub two right parenthesis squared plus left parenthesis y sub one minus y sub two right parenthesis squared end square root

A. V(8, −4)
B. X(5, −2)
C. Y(−6, 0)
D. Z(5, 7)

Answers

the equation of a cirecle with radius r and center at (h,k) is
(x-h)^2+(y-k)^2=r^2
r=10
center=(-2,-4)
(x+2)^2+(y+4)^2=10^2
(x+2)^2+(y+4)^2=100
(x,y)
sub given points (or use TI) and see if you get a true statmeent
A is on it

answer is A

the equation of of circle = (x+2)^2 + (x+4)^2 = 100 
by sub. by this points in the circle equation 
for point V(8,-4) 
(8+2)^2 + (-4+4)^2 = 100 
so the point V lay on the circle 

Complete the following item based on the given information.The volume of a box(V) varies directly with its length(l). Using k for the constant of proportionality, express the relationship between V and l if V varies directly with l.
V = _______

Answers

Answer:

V = kl

Step-by-step explanation:

The direct variation states:

if y \propto x , then the equation is in the form of:

y=kx; where k is the constant of proportionality.

As per the statement:

The volume of a box(V) varies directly with its length(l).

V \propto l

Using the above definition we have;

V = kl

where,

k represents for the constant of proportionality.

Therefore, the relationship between V and l if V varies directly with l is,

V = kl

Volume\ V\ varies\ directly\ with\ length\ l\ proportion\ is\n\n (V)/(l)=k\ \ |*l\n V=kl

Simplify the radical expression(8+√11)(8-√11)

A.53
B.75+16√11
C.-57
D.64+√11

Answers

(8 + √11)(8 - √11)
8^2 - √11^2
64 - √11^2
64 - 11
53

The answer is: 53.
(8 + root11)(8 - root11) =
64 - root11 + root11 - 11 =
64 - 11 = 53

Answer A.

Is x+1 a factor of the function f(x)=2x⁵-4x⁴+9x³-x+13?Show work supporting your answer.

Answers

Answer:

(x+1) will not be factor of given polynomial

Step-by-step explanation:

We have given polynomial f(x)=2x^5-4x^4+9x^3-x+13

We have to find that  is (x+1) factor of the given polynomial

If (x+1) will be the factor of the polynomial then x= -1 will be the root of the polynomial

And if we put x =-1 in the pronominal then then its value will be zero

f(-1)=2(-1)^5-4(-1)^4+9(-1)^3-(-1)+13=-2-4-9+1+13=-1

So (x+1) will not be factor of given polynomial

If (cos)x= 1/2 what is sin(x) and tan(x)? Explain your steps in complete sentences.

Answers

The correct answers are:
1) sin(x) = ( √(3) )/(2)
2) tan(x) = √(3)

Explanation:
Given:
cos(x) =  (1)/(2)

Step 1:
Since, according to the Trigonometric identity:
sin^2(x) + cos^2(x) = 1 -- (1)

Step 2:
Plug in the value of cos(x) in equation (1):
sin^2(x) + ( (1)/(2) )^2 = 1 \n sin^2(x) + (1)/(4) = 1 \n sin^2(x)  =  (3)/(4)

Step 3:
Take square-root on both sides:
√(sin^2(x)) =  \sqrt{(3)/(4)}

sin(x) = ( √(3) )/(2)

Now to find the tan(x), we would use the following formula:

tan(x) = (sin(x))/(cos(x)) --- (2)

Plug in the values of sin(x) and cos(x) in equation (2):
tan(x) = ( ( √(3) )/(2) )/( (1)/(2) )

Hence tan(x) = √(3)

Answer:

The value of \sin x=(√(3))/(2)

The value of \tan x=√(3)

Step-by-step explanation:

Given = \cos x=(1)/(2)

To find :\sin x=? and \tan x=?

Solution:

We know that, if the cosine function of an angle is(1)/(2) then the angle is equal to the 60°.

\cos x=(1)/(2)

x = 60°

The value of the :

\sin x=\sin 60^o=(√(3))/(2)

We know that ratio of sine function to the cosine function is equal tto the tangent

\tan x=(\sin x)/(\cos x)=((√(3))/(2))/((1)/(2))=√(3)

The value of \sin x=(√(3))/(2)

The value of \tan x=√(3)

Y=3x 2x+y=15
Can you please help with this? It's confusing. It's soling systems of equations by substitution

Answers

so you subtitute y=3x into
2x+y=15
so
2x+(3x)=15
add like terms
5x=15
divide both sides by 5
x=3

subtitute x=3 into first equation (y=3x)
y=3(3)
y=9
it's simple jus plug in 3x into Y and u will have 2x+3x=15 
                                                                              5x=15
                                                                               the answer(x=3)